Preparation and Oxidation Resistance of Mo-Si-B Coating on Nb-Si Based Alloy Surface - PANG Jie; ZHOU Chun-gen (Cailiao gongcheng, 2018)
Mo-Si-B coating was prepared on Nb-Si alloys to improve the high-temperature oxidation. The influence of the halide activators (NaF and AlF3) on Si-B co-depositing to obtain Mo-Si-B coating on Nb-Si alloys was analyzed by thermochemical calculations. The results show that NaF proves to be more suitable than AlF3 to co-deposit Si and B. Then Mo-Si-B can be coated on Nb-Si based alloys using detonation gun spraying of Mo followed by Si and B co-deposition. The fabricated coatings consist of outer MoSi2 layer with fine boride phase and inner unreacted Mo layer. The mass gain of the Mo-Si-B coating is 1.52mg/cm2 after oxidation at 1250℃ for 100h. The good oxidation resistance results in a protective borosilicate scale formed on the coating.